Motif Wanita Rawan Sosial dan Ekonomi Dalam Komunitas Ikatan Janda Muslimah Ponorogo (IJMP) - Yusuf Adam Hilman (SIMULACRA: JURNAL SOSIOLOGI, 2018)
This research was conducted in Ponorogo Regency on the organization of the Ponorogo Muslimah Widow Association (IJMP). To obtain data, this study used interview techniques with purposive sampling technique. The results of this study show that there are 2 (two) models of actions that become the motives of IJMP members, namely: 1) rational actions, and 2) non-rational actions. Rational actions are divided into two, namely, instrumental rational actions, which describe conscious choice, and value-oriented actions, which describe efficiency and effectiveness. Non-rational actions are also divided into two, actions that are related to customs and beliefs, and actions that are dominated by personal feelings. The reason must be a strong woman: to survive and believe in religious teachings. HJMP members have consideration of rational and non-rational actions and in groups they try to maintain their chosen social actions.